Achieving Efficient Incorporation of π‐Electrons into Graphitic Carbon Nitride for Markedly Improved Hydrogen Generation. (3rd January 2019) - Li, Jing; Wu, Dandan; Iocozzia, James; Du, Haiwei; Liu, Xueqin; Yuan, Yupeng; Zhou, Wei; Li, Zhen; Xue, Zhaoming; Lin, Zhiqun
Abstract: A rapid and highly efficient strategy for introducing C into g‐C3 N4 involves copolymerizing π‐electron‐rich barbituric acid with melamine via a facile microwave‐assisted heating, thereby eliminating the issues in conventional electric furnace heating, such as the severe volatilization, owing to the mismatch of the sublimation temperatures of barbituric acid and melamine. The g‐C3 N4 catalyst after optimizing the C‐doping content actively generates increased amounts of H2 under visible light exposure with the highest H2 generation rate of 25.0 μmol h −1, which is nearly 20 times above that using g‐C3 N4 produced by conventional electric furnace heating of two identical monomers (1.3 μmol h −1 ). As such, the microwave‐assisted heating strategy may stand out as an extremely simple route to incorporating π‐electrons into g‐C3 N4 with markedly improved photocatalytic performance.